From risk to reward: Unveiling the multidimensional impact of financial risks on the performance of Ghanaian banks - Benjamin Blandful Cobbinah; Wen Yang; Francis Atta Sarpong; George Nyantakyi (Heliyon)
The Ghanaian banking sector, grappling with a spectrum of financial risks, presents a compelling case study for understanding the dynamics of risk and profitability in emerging markets. This study seeks to fortify the financial performance of Ghanaian banks through an innovative application of benchmark regression analysis, focusing on critical financial risk and performance metrics. Employing an explanatory research methodology, we harnessed a panel regression model to scrutinize secondary data extracted from the annual income statements of 23 banks, spanning nearly two decades from 2006 to 2023. Our analytical arsenal encompassed the fixed effects model, the Generalized Method of Moments (GMM) within a fixed-effects framework, and Pooled Ordinary Least Squares (POLS) to ensure methodological rigor and robustness. Our findings illuminate the relationship between financial risks and Return on Equity (ROE). Specifically, credit risk was found to exert a significant positive influence on ROE, suggesting that judicious credit extension can be a conduit for profitability. In contrast, liquidity risk was identified as a determinant negatively impacting ROE, underscoring the imperative for effective liquidity management to safeguard banks' long-term solvency. Additionally, market risk was observed to have a positive association with ROE, indicating that strategic exposure to market volatility can potentially enhance financial performance. The implications of this study are manifold, offering actionable insights for policymakers and stakeholders in the banking sector. It advocates for a recalibrated approach to risk management, where banks proactively embrace credit risk while vigilantly addressing liquidity challenges. The study further posits that by forging strategic interconnections, banks can augment their risk management capabilities, thereby bolstering their financial performance and ensuring resilience in the face of market volatility.